Answer:
x = 2
Explanation:
Rewrite the equation as 4x - 6 = 2
Move all terms not containing x to the right side of the equation:
Add 6 to both sides of the equation.
4x = 2 + 6
Add 2 and 6.
4x = 8
Divide each term by 4 and simplify.
Divide each term in 4x = 8 by 4.
![(4x)/(4) =(8)/(4)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/xx14xciaabnu2zc5ucsw74dx2xyc5s6r8u.png)
Reduce the expression by cancelling the common factors.
![x=(8)/(4)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/it3gcnz14ka8uf42xst59knvrd2zizrtp1.png)
Divide 8 by 4.
x = 2